A modified PV fed 9 level inverter for standalone applications with reduced number of switches - V, Jaikrishna; Sekhar Dash, Subhranhsu; T Alex, Linss (International Journal of Engineering and Technology, 2017)
The power crisis in India is increasing at an alarming rate. Solar power is a domestic source of energy and its availability throughout the year makes it a primary target to solve this crisis. It will never produce any hazardous waste and it won’t pollute the air. But various issues like Power quality problems and Harmonic distortion seep in due to the intermittent nature of PV system. Multi-Level Inverter (MLI) gives solution for PQ issues and helps in high power handling capabilities. In this work a new multilevel inverter topology is proposed. The controlled pulses are generated through sinusoidal PWM techniques. The proposed topology is implemented and the controlled circuit is simulated in MATLAB/SIMULINK. The same is realized in the hardware circuit having a cost effective dsPIC30F2010 digital controller. The proposed topology consists of only seven power electronic switches and that is the main advantage of this topology. The Simulation results and the Hardware results reveal that the suggested technique is highly advantageous.